Empirical Analysis of Workplace Conflict and its Influence on the Attitude of Media Employees in Ghana - Anku Tsede, O. (Journal of Management Policy and Practice, 2016)
Workplace conflict is known to have severe implications on employees and organisations worldwide. Conflicts at the workplace have resulted in the destruction of cordial relationships among working colleagues as well as subordinates and superiors and has also changed enthusiastic employees to rather hostile and ineffectual actors. Consequently, these employees are not able to meet their targets due to negative attitudinal changes towards work, thus hampering the attainment of organizational goals. However, there is little empirical studies on this subject in both academic and industrial circles. In examining the outcomes of workplace conflict and its influence on the attitudes of media employees, thispaper employed qualitative methodologies to select forty two (42) respondents from six Ghanaian print and electronic privately and state owned media houses. Findings revealed that attitudes of employees towards work were predominantly influenced negatively as employees decline in commitment to work and cooperation with others. Further, following conflicts, employees engaged in many adverse behavioral tendencies including not being on talking terms, not greeting one another, hostile behaviours and insecurity. Nonetheless, the paper interestingly found some positive outcomes such as idea sharing, unity, activeness and alertness from conflicts.